A Case Report on the Management of Gridhrasi (Disc Bulge of Lumbosacral Spine) through Ayurvedic Interventions - , Anita Yadav (International Research Journal of Ayurveda & Yoga, 2025)
Disc bulge is a common spinal condition that causes symptoms from mild to severe pain and functional limitation due to nerve root compression affecting an individual’s mobility. In Ayurveda, it is a Vata vitiated condition characterized by pain radiating along the sciatic nerve. It affects the lower back, hips, and legs associated with numbness, tingling sensation, and muscle weakness. This case study examines the clinical presentation, diagnosis, and treatment of a female patient aged 55 years with a lumbar disc bulge with an annular tear. Here the patient presented with persistent lower back pain radiating to the lower extremities, along with a tingling sensation which used to get worse with physical activity in the past 1 year. Diagnostic imaging magnetic resonance imaging, confirmed with disc bulge at L3-L4, L4-L5, and L5-S1 and a posterior annular tear. Physical therapy and lifestyle adjustments were initially employed as conservative treatment. She was managed with oral medications including Trayodashang Guggulu 2 tablets thrice daily, Punarnavadi Mandoor 2 tablets thrice daily, and Dashmool Kwath 40 mL twice, along with Sarvanga Abhyang (oleation therapy) and Sarvanga Swedana (sudation therapy). The study also discusses the patient’s clinical progression, treatment protocol, and recovery outcomes in managing disc bulge with annular tear effectively.